Price setting in German manufacturing: new evidence from new survey data - Harald Stahl (Deutsche Bundesbank, 2005)
This paper presents new evidence on the formation of producer prices based on a onetime survey that was conducted on a sample of 1200 German firms in manufacturing in June 2004. Most of the firms have price-setting power and apply mark-up pricing. Indexation is negligible. Fixed nominal contracts are the most important reason for postponing a price adjustment. The second most likely reason is coordination failure, which causes more upward than downward stickiness. For every second firm both reasons are important. Firms can be assigned to four different groups according to an increasing complexity of reasons of price stickiness.
Keywords: D40; E30; 330; Price rigidity; cluster analysis; Verarbeitendes Gewerbe; Betriebliche Preispolitik; Preisrigidität; Deutschland